THE IMPACT OF STRATEGIC PLANNING ON SOCIAL RESPONSIBILITY: AN APPLIED STUDY IN THE MINISTRY OF EDUCATION - DIRECTORATE GENERAL OF EDUCATION IN DHI QAR - Habeeb wateen Mankhi Al-Rikabi; Imad Jasser Awda Al-Hadidi (Scholar Express Journals, 2024)
This study addresses the impact of strategic planning on social responsibility in the Dhi Qar Education Directorate, where reliable and effective measurement tools were used. The results showed that the reliability coefficient was 0.992, indicating high overall reliability, while the validity coefficient was 0.996, reflecting high accuracy in the measurements. The results also showed good reliability when dividing the tool into two halves, as the value reached 0.908, which enhances the credibility of the results. The results indicated that there was a general positive agreement among sample members regarding the strategic planning paragraphs, as the overall average was 3.59 with a standard deviation of 1.45, indicating strong support for all dimensions related to planning. However, some areas, such as reviewing strategic plans, showed a need for improvement. As for social responsibility, the overall average was 3.56 with a standard deviation of 1.43, reflecting agreement among employees regarding the effectiveness of social responsibility practices. The results also showed a strong positive relationship between strategic planning and social responsibility, as the correlation coefficient reached 0.889, indicating significant significance. When analyzing the regression model, the arithmetic value of (F) for strategic planning was 1396.014, indicating a strong significant effect, while (R2) was 0.825, which means that 82.5% of the changes in social responsibility can be explained by strategic planning. Finally, Kolmogorov-Smirnova and ShapiroWilk tests confirmed that the data follow a normal distribution, which supports the reliability of the results.
Keywords: Strategic Planning; Social Responsibility; Applied Study